2010
DOI: 10.5539/ibr.v3n3p100
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sustainable Development on Retail Store Image

Abstract: This article explores young consumers' perceptions of the sustainable development (SD) initiatives of French food retailers and evaluates their impact on the brand image of the retailers and their relationships with consumers. The methodology incorporated the analysis of the websites of the main French food retailers, a press review, eight in-depth interviews and a face-to-face survey. The findings highlight that young consumers tend to link SD more to ecology and less to social and economic issues. When a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
0
15
2
2
Order By: Relevance
“…Nilai atau harga saham suatu perusahaan dipengaruhi oleh aset berwujud dan tidak berwujud (Hsu et al, 2013). Brand image yang baik dimata konsumen merupakan salah satu aset tidak berwujud perusahaan yang akan memberikan persepsi positif konsumen sehingga memicu konsumen untuk mengevaluasi dan memilih produk/jasa perusahaan (Porter & Claycomb, 1999). Kepuasan dan loyalitas pelanggan akan berdampak pada kinerja keuangan (Suranto et al, 2017).…”
Section: Pendahuluanunclassified
“…Nilai atau harga saham suatu perusahaan dipengaruhi oleh aset berwujud dan tidak berwujud (Hsu et al, 2013). Brand image yang baik dimata konsumen merupakan salah satu aset tidak berwujud perusahaan yang akan memberikan persepsi positif konsumen sehingga memicu konsumen untuk mengevaluasi dan memilih produk/jasa perusahaan (Porter & Claycomb, 1999). Kepuasan dan loyalitas pelanggan akan berdampak pada kinerja keuangan (Suranto et al, 2017).…”
Section: Pendahuluanunclassified
“…Further evidence was confirmed by Hoeffler and Keller (2002) who found that corporate social marketing can improve brand image. CSR was also underlined as a fundamental aspect in retail management (Cacho-Elizondo & Loussaïef, 2010;Keller, 2003) and brand image (Anselmsson & Johansson, 2007). Active involvement in CSR activities enables a retailer to strengthen its brand reputation and manage customer relationships (Anselmsson & Johansson, 2007;Elg & Hultman, 2016;Piacentini, MacFadyen, & Eadie, 2000).…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…Le manque de connaissances des engagements et actions menées par les distributeurs en matière de RSE et leur niveau de méfiance ou de scepticisme envers ceux-ci peuvent l'expliquer (Lavorata, 2016). Les consommateurs reconnaissent néanmoins que les distributeurs font des efforts pour communiquer sur leurs engagements et actions en matière de RSE (Cacho-Elizondo et Loussaïef, 2010).…”
Section: L'attitude à L'égard Des Mdd De Terroir Et L'image Prix Du Munclassified